Mathematical Model and Solution for Fingering Phenomenon in Double Phase Flow through Homogeneous Porous Media - Piyush R. Mistry; Vikas H. Pradhan; Khyati R. Desai (The Scientific World Journal)
The present paper analytically discusses the phenomenon of fingering in double phase flow through homogenous porous media by using variational iteration method. Fingering phenomenon is a physical phenomenon which occurs when a fluid contained in a porous medium is displaced by another of lesser viscosity which frequently occurred in problems of petroleum technology. In the current investigation a mathematical model is presented for the fingering phenomenon under certain simplified assumptions. An approximate analytical solution of the governing nonlinear partial differential equation is obtained using variational iteration method with the use of Mathematica software.